Artikel Review : Analisis Pemeliharaan Alat Kesehatan - Dewi Rahmawati; Marthy Meliana; Maria Fransiska Silviani; Fina Nikmatul Wasi’ah; Niken Rahmita Khairani; Sari Fatul Layly; Safanda Tiara Fitri; Miya Hartini Nur Wakhid; Oktafia Damayanti; Ewalde Yovita Bria; Silvi Novita Permatasari; Magdalena Kasmin Belaon (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Health equipment is one of the factors that plays an important role in providing health services to the community. Maintenance is an activity that aims to maintain or ensure that the condition of the building and its facilities and infrastructure is in good condition, can operate properly, and is acceptable to existing standards. In this analysis, the method used is based on a literature review from electronic data sources. Several factors related to ensuring the quality of medical equipment in health care settings are monitoring the maintenance of medical and non-medical equipment, timely calibration or validation of instruments/measuring tools.